Endovascular treatment of traumatic carotid cavernous fistula with trapping technique (Medical Journal of Indonesia, 2013)
Conventional endovascular treatment for carotid cavernous fistula (CCF) involves a direct delivery of either coils, detachable balloon or both to the fistula with end point of CCF resolution and carotid artery preservation. But in few cases with severe laceration of carotid artery, the feasible endovascular technique applicable is by blocking the filling of fistula from cerebral circulation. This method known as trapping technique which implicates carotid artery occlusion, was performed in our present case with good result. (Med J Indones. 2013;22:178-82. doi: 10.13181/mji.v22i3.588)